2003
DOI: 10.1074/jbc.m209803200
|View full text |Cite
|
Sign up to set email alerts
|

Okazaki Fragment Maturation in Yeast

Abstract: To address the different functions of Pol ␦ and FEN1 (Rad27) in Okazaki fragment maturation, exonucleasedeficient polymerase Pol ␦-01 and Pol ␦-5DV (corresponding to alleles pol3-01-(D321A, E323A) and pol3-5DV-(D520V), respectively) were purified and characterized in this process. In the presence of the replication clamp PCNA, both wild-type and exo ؊ Pol ␦ carried out strand displacement synthesis with similar rates; however, initiation of strand displacement synthesis was much more efficient with Pol ␦-exo ؊… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
96
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(104 citation statements)
references
References 33 publications
6
96
0
1
Order By: Relevance
“…Therefore, it is conceivable that the hBLM͞scFEN1 interaction at the replication fork leads to either enhanced cleavage by scFEN1 or enhanced recruitment of scFEN1 to the flap, effectively raising the local concentration of the protein and reducing the need for scDna2. Suggesting that some component of the maturation system, such as a helicase, may be missing in vitro, pol ␦ cannot strand displace rapidly enough in a reconstituted model system containing purified pol ␦, proliferating cell nuclear antigen, RFC, FEN1, Dna2, and ligase to account for rates of Okazaki fragment maturation in vivo (25,26). Thus, hBLM might stimulate flap formation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, it is conceivable that the hBLM͞scFEN1 interaction at the replication fork leads to either enhanced cleavage by scFEN1 or enhanced recruitment of scFEN1 to the flap, effectively raising the local concentration of the protein and reducing the need for scDna2. Suggesting that some component of the maturation system, such as a helicase, may be missing in vitro, pol ␦ cannot strand displace rapidly enough in a reconstituted model system containing purified pol ␦, proliferating cell nuclear antigen, RFC, FEN1, Dna2, and ligase to account for rates of Okazaki fragment maturation in vivo (25,26). Thus, hBLM might stimulate flap formation.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro reconstitution of the processing reaction showed that, if the flap was Ͼ30 nt, then Dna2 was required to stimulate the endonucleolytic activity of FEN1; however, Dna2 had no effect if the flap was Ͻ30 nt (24,25). Thus, Dna2 is likely to be essential for Okazaki fragment maturation only in cases where FEN1 activity is somehow impaired (25,26).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…pol ␦ displaces relatively short flaps, which are cleaved by FEN1 as they are created, leaving a nick for LigI (7)(8)(9). FEN1 binds at the 5Ј-end of the flap and tracks down the flap cleaving only at the base (5,10,11).…”
mentioning
confidence: 99%